Formulation of floating metronidazole microspheres using cassava starch (manihot esculenta) as polymer (2017)
" Floating gastroretentive microspheres have been used to prolong the gastric residence time after oral administration and improve the local effect of metronidazole in the stomach in the treatment of peptic ulcer caused by Helicobacter pylori. In the present study, cassava starch, obtained from the tubers of Manihot esculenta has been pregelatinized and used as polymer in combination with sodium alginate for the formulation of floating gastroretentive metronidazole microspheres. Metronidazole microspheres were prepared by ionic gelation method using pregelatinized cassava starch and sodium alginate at different concentrations as polymers and calcium chloride (2% w/v) as chelating agent. Sodium bicarbonate (2% w/w) was used as gas releasing agent. Microspheres were characterized using the particle size, swelling index, floating lag time (FLT), total floating time and drug release properties. Spherical discrete microspheres with size ranging from 1.52 to 2.23 mm were obtained with FLT of less than 5min and drug entrapment efficiency of 42–60% w/w. The microsphere maintained buoyancy for over 19h and the microspheres provided controlled release of metronidazolefor up to 18h. Drug release from the microspheres, swelling index and buoyancy depended on the concentration of cassava starch in the polymer blend. Formulations containing high concentration of cassava starch showing shorter floating lag time and faster drug release. Thus, buoyancy and rate of drug release appeared to be modulated by the concentration of cassava starch in the polymer blend. The results showed that pregelatinized cassava could be useful in the formulation of floating gastroretentive metronidazole microspheres "